SPIN-POLARIZED PHOTOCURRENT THROUGH QUANTUM DOT PHOTODETECTOR - Hieu, Nguyen Van; Ha, Nguyen Bich (ASEAN Journal on Science and Technology for Development, 2007)
The theory of the photocurrent through the photodetector based on a two-level semiconductor quantum dot (QD) is presented. The analytical expressions of the matrix elements of the electronic transitions generated by the absorption of the circularly polarized photons are derived in the lowest order of the perturbation theory with respect to the electron tunneling interaction as well as the electron-photon interaction. From these expressions the mechanism of the generation of the spin-polarized of electrons in the photocurrent is evident. It follows that the photodetector based on the two-level semiconductor QD can be used as the model of a source of highly spinpolarized electrons.